MUSIC LESSON AT SCHOOL AND ITS TASKS - Nematjonova Shukurxon (TADQIQOTLAR, 2025)
Annotation: In our country, great importance is attached to the successful solution of issues of aesthetic education - an important component of educating the younger generation in the spirit of love for the motherland. Music is one of the most important parts of aesthetic education, which requires children to be close to music, to teach them to understand and perform works of music from an early age. At the same time it teaches to think independently and work independently. The article describes the music lesson at school and its tasks.